Current Insight into the Dynamics of Secondary Endodontic Infections - Alexandru Andrei Iliescu; Irina Maria Gheorghiu; Sergiu Ciobanu; Ion Roman; Anca Silvia Dumitriu; Stana Păunică (Journal of Mind and Medical Sciences, 2025)
Background/Objectives: The aim of this narrative review is to perform an updated literature review of the root canal microbiome in secondary endodontic infections and the bacterial dynamics that govern the processes leading to the development of these persistent endodontic infections and periapical lesions. Methods: A literature search of scientific publications issued in the last 8 years, i.e., 2017–2024, was conducted in PubMed (MEDLINE) and ScienceDirect databases, using the following keywords: endodontic microbiome; endodontic pathogens; periapical lesion; primary endodontic infection; secondary/persistent endodontic infection; functional redundancy. Discussions: Secondary endodontic infections (SEIs) are a highly prevalent pathological condition affecting a minimum of one tooth in more than half of adults worldwide. The transition from primary endodontic infection (PEI) to secondary endodontic infection (SEI) is mainly governed by Enterococus faecalis (EF) that invades and dominates the previous endodontic biofilm initiated by Fusobacterium nucleatum (FN). Conclusions: The findings from different studies indicate that secondary endodontic infections are polymicrobial. In SEIs, the microbial species interactions are crucial in influencing the ecology of infected root canals. The issue of the keynote pathogen is still under debate. Both EF and FN pathogens cooperate with neighboring residents. Functional redundancy of the endodontic microbiome explains how the ecological diversity modulates its pathogenicity.